2001
DOI: 10.1152/ajpendo.2001.280.1.e103
|View full text |Cite
|
Sign up to set email alerts
|

Increasing membrane-bound MCSF does not enhance OPGL-driven osteoclastogenesis from marrow cells

Abstract: Macrophage colony-stimulating factor (MCSF) and osteoprotegerin ligand (OPGL), both produced by osteoblasts/stromal cells, are essential factors for osteoclastogenesis. Whether local MCSF levels regulate the amount of osteoclast formation is unclear. Two culture systems, ST-2 and Chinese hamster ovary-membrane-bound MCSF (CHO-mMCSF)-Tet-OFF cells, were used to study the role of mMCSF in osteoclast formation. Cells from bone marrow (BMM) or spleen were cultured with soluble OPGL on glutaraldehyde-fixed cell lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…Thus, the stimulation of bone resorption during the anabolic protocol should be a transient event preceding osteoblastic bone formation to provide new remodeling sites for new incoming osteoblasts. As mentioned earlier, it is well documented that the increase in osteoclast formation is directly proportional to the level of RANKL expression, and M-CSF plays primarily a permissive role (29,32). Furthermore, both in vitro and in vivo studies have demonstrated that PTH influences osteoclast formation primarily by regulation of the RANKL/OPG ratio (33).…”
Section: Discussionmentioning
confidence: 87%
“…Thus, the stimulation of bone resorption during the anabolic protocol should be a transient event preceding osteoblastic bone formation to provide new remodeling sites for new incoming osteoblasts. As mentioned earlier, it is well documented that the increase in osteoclast formation is directly proportional to the level of RANKL expression, and M-CSF plays primarily a permissive role (29,32). Furthermore, both in vitro and in vivo studies have demonstrated that PTH influences osteoclast formation primarily by regulation of the RANKL/OPG ratio (33).…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, cortisol can increase the expression of RANKL (receptor activator of NF-κB ligand, which enhances osteoclastogenesis) and enhance the expression of the macrophage colony-stimulating factor (MCSF). Previous studies have shown that the RANKL (Receptor Activator for Nuclear Factor-κB Ligand), MCSF (Macrophage Colony Stimulating Factor) and TGF β (Transforming Growth Factor-β) pathways played critical roles in osteoporosis (Figure 5) [15,27,28,29]. Therefore, we further elucidated whether these five secreted protein signalling pathways were implicated in bone fractures of CD.…”
Section: Resultsmentioning
confidence: 94%
“…46 However, increased csCSF-1 expression did not enhance receptor activator of nuclear factor-B (NF-B) ligand (RANKL)-driven osteoclastogenesis from marrow cells in another case. 47 Osteopetrotic (Csf1 op /Csf1 op ) mice harbor an inactivating mutation in the coding region of the CSF-1 gene and are CSF-1 deficient. [48][49][50] They are osteopetrotic due to their paucity of osteoclasts.…”
Section: Introductionmentioning
confidence: 99%